2014
DOI: 10.1038/pr.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk markers until 12 mo of age in infants fed a formula supplemented with bovine milk fat globule membranes

Abstract: Background: Some of the health advantages of breast-fed as compared to formula-fed infants have been suggested to be due to metabolic programming effects resulting from early nutrition. Methods: In a prospective double-blinded randomized trial, 160 infants <2 mo of age were randomized to experimental formula (EF) with added milk fat globule membrane (MFGM) or standard formula (SF) until 6 mo of age. A breast-fed reference (BFR) group consisted of 80 infants. Measurements were made at inclusion and at 4, 6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 45 publications
4
53
1
1
Order By: Relevance
“…MFGM supplementation to infant formula had no effects on infant growth, weight gain, body mass index, and few effects on metabolic parameters such as cholesterol serum level in healthy infants compared with infant formula group. 23,65 Besides, other reports also showed that maternal diet supplemented with bioactive compounds such as grape seed procyanidin or resveratrol had weak effects on the biometric parameters and plasma parameters associated with metabolic disturbance in offspring born to healthy dams but obviously ameliorated metabolic impact of maternal obesity in offspring, which were consistent with our results. 20,66 In our study, the effects of MFGM-PL to HFD dams were focused on male offspring, which are more susceptible to adiposity changes associated with metabolic programming.…”
Section: Discussionsupporting
confidence: 91%
“…MFGM supplementation to infant formula had no effects on infant growth, weight gain, body mass index, and few effects on metabolic parameters such as cholesterol serum level in healthy infants compared with infant formula group. 23,65 Besides, other reports also showed that maternal diet supplemented with bioactive compounds such as grape seed procyanidin or resveratrol had weak effects on the biometric parameters and plasma parameters associated with metabolic disturbance in offspring born to healthy dams but obviously ameliorated metabolic impact of maternal obesity in offspring, which were consistent with our results. 20,66 In our study, the effects of MFGM-PL to HFD dams were focused on male offspring, which are more susceptible to adiposity changes associated with metabolic programming.…”
Section: Discussionsupporting
confidence: 91%
“…Such trend disappears in childhood and even shifts in adolescence and adulthood where the grown‐up breast‐fed infants have lower total serum cholesterol concentration in comparison with a formula‐fed group . Very recently, Timby et al showed in a prospective double‐blinded randomized trial ( N = 160 infants, 2–12 months of age) that increasing cholesterol intake between 2 and 6 months of age via the supplementation of an experimental infant formula with bovine MFG membrane induced an higher total serum cholesterol concentration similar to the one observed in breast‐fed infants without modification of the LDL/HDL ratio. The experimental infant formula was also reduced in energy and protein content compared to the standard formula.…”
Section: The Specificity Of Milk Lipid Structure In Human Milkmentioning
confidence: 79%
“…42 During the intervention, the EF group gradually reached higher serum cholesterol concentrations than the SF group, and there was no significant difference between the EF and BFR group at 6 months of age. 43 At 4 months of age, the BFR group had higher levels of Lactobacillus gasseri in the oral microflora, but there was no difference between the EF and SF groups. 46 In a multicenter noninferiority DBRCT on 199 (149 fulfilled the intervention) healthy term infants, Billeaud et al 44 evaluated the safety of 2 infant formulas enriched with a lipid-rich MFGM (MFGM-L) or a MFGM-P bovine fraction, respectively.…”
Section: Clinical Studies On Mfgm Concentrates Fed To Infants and Chimentioning
confidence: 86%